THE ROLE OF GOVERNMENT INLAM MANAGING A DEMOCRACY SOCIETY - aleng, Aleng (Unmul Civic Education Journal, 2022)
Discusses the realization of the role of the community in the implementation of democratic local government. The problem that occurs is that the realization of the role of the community in the implementation of democratic regional government is not yet fully regulated in the rule of law in Indonesia, thus causing confusion about the role of the community in implementing regional government in carrying out democratic regional autonomy. This paper aims to understand and understand the realization of the role of the community in the administration of democratic local government. This writing uses a normative legal research method with the type of analysis approach to legislation (State approach). This paper produces research that in democracy is the government of the people by giving the community authority through the realization of participation. Democracy in the system of government means government of the people. Democracy can foster a sense of belonging to the community and be responsible for development in accordance with the meaning of democracy, namely government from, by and for the people. The process of implementing programs and implementing development in local government democracy based on community participation includes program planning and implementation, dialogue with the public and decision making.